2020
DOI: 10.1504/wrstsd.2020.105584
|View full text |Cite
|
Sign up to set email alerts
|

The triple helix approach in the defence industry: a case study at the Brazilian Army

Abstract: As in many other industries, technological innovation plays an important role in the economic development of the defence industry. In recent years, the Brazilian Army has adopted the triple helix model and open innovation as cooperation models in research in order to generate innovation, involving the army research efforts, the defence industry and academia. Inspired on a Swedish model, one of the most recent army's initiatives to stimulate innovation was the creation of an open innovation arena in order to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…First, the relevance of CE in the defense industry is evident, in contrast to the lack of theoretical discussion in this regard. In addition, we found several articles discussing the importance of the triple helix [47][48][49], however, this article introduces new evidence that justifies further research to verify whether the EU defense industry operates within the framework of a quintuple helix. Thus, the focus of this article is on the presentation of "technology" and the "circular economy" as possible helices.…”
Section: Theoretical and Managerial Contributionsmentioning
confidence: 92%
See 1 more Smart Citation
“…First, the relevance of CE in the defense industry is evident, in contrast to the lack of theoretical discussion in this regard. In addition, we found several articles discussing the importance of the triple helix [47][48][49], however, this article introduces new evidence that justifies further research to verify whether the EU defense industry operates within the framework of a quintuple helix. Thus, the focus of this article is on the presentation of "technology" and the "circular economy" as possible helices.…”
Section: Theoretical and Managerial Contributionsmentioning
confidence: 92%
“…The existing literature argues that the defense industry is operating in a triple helix, i.e. universities, governments and industry (Figure 2) [47][48][49]. Thus, civil society and environment are not found in Figure 2 as the figure is limited to the triple helix.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The topics responsible for the growing number of publications since 2018 are mainly related to defence innovation and technology transfer of the Spanish defence industry (Briones-Peñalver et al 2020;Oliva et al 2019;Callado-Muñoz et al 2020), the expansion of the Chinese Defence industry (Béraud-Sudreau and Nouwens 2021; Dominese 2020), and the Brazilian R&D projects (Bernat and Karabag 2018;Silva and Olavo-Quandt 2019;Fernandes et al 2020). The most notable investment in research refers to the Spanish defence industry, which is also shown in Figure 3 (top 3 countries).…”
Section: Findings From the Slrmentioning
confidence: 99%
“…Thus, very few studies similar to this one have been identified. Worthy of note is the Triple Helix (TH) approach Leydesdorff 1995, 2000) used by the Brazilian Army (Fernandes et al 2020), which stimulated innovation between the Army, the defence industry, and the academy. Similar research was conducted in Portugal with a paper that analyses the relationship (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation